(untitled) (Jurnal Bina Praja, 2025)
Risk management in local government is increasingly positioned as a strategic instrument for strengthening governance, integrity, and the quality of public decision-making. However, various studies show that increased regulation and maturity of risk management systems do not always translate into substantive improvements in governance and behavioral risk control. This study aims to analyze the effectiveness of risk management policies in the East Kalimantan Provincial Government by examining the suitability of policy design, variations in implementation across regional institutions, and their impact on governance and government integrity. The study uses a qualitative, descriptive, evaluative approach through case studies of four strategic regional institutions. Data was collected through in-depth interviews, limited participant observation, and document analysis. Data was analyzed using an interactive model. The results of this study indicate that the risk management policy in the East Kalimantan Provincial Government is normatively aligned with international standards and has successfully increased the maturity of the internal control system. However, the policy’s effectiveness still varies across regional agencies and has not fully strengthened integrity, as reflected in the paradox between increasing system maturity and decreasing corruption control effectiveness. This finding confirms that risk management has not been fully internalized as a culture and strategic decision-making instrument. In conclusion, strengthening risk management requires a shift from an administrative compliance approach to a reflective, integrated policy-learning approach. It is also recommended that policies be more directed at strengthening risk leadership, the role of the Inspectorate as a risk enabler, integrating risk into planning and budgeting, and developing a risk-aware culture, particularly across regional agencies within the East Kalimantan Provincial Government.